Distance learning as a stage of academic development and innovation in higher education: Approach to a general focus for the evaluation of innovation - González Enders, Ernesto; Millán Velásquez, Luis (Formazione & insegnamento, 2012)
In the framework of regional declarations, agreements, and policies that promote innovation, the use of TIC and the development of distance learning in higher education, it is possible to think about two different modes of contemporary teaching approach: as a regular modality per se and as an academic development space and innovation. We emphasize this second approach as an institutional atmosphere constituted by ambiances associated to development of the distance learning: how to teach and learn; the curriculum; institutional technological media; the systemic organization; the research; and the management system of information and knowledge. These ambiances are permeable to innovation, derived from its own enterprise as a consequence of it developments. It is very important to attend to the evaluation of these innovative impacts, and from there it can be reached a framework that helps to the systemic character of distance learning and to the dynamic conception and non linear behavior of the innovation. We also illustrate that by showing an integrated assessment approach that was applied in the SEDUCV, whose traits are presented in order to characterize our conceptual proposal in a practical way. The quasi-totality of these traits has an empirical referent for the development of this case.